2016
DOI: 10.1038/srep39482
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index Predicts Prognosis of Patients with Esophageal Squamous Cell Carcinoma: A Propensity Score-matched Analysis

Abstract: Systemic immune-inflammation index (SII), based on peripheral lymphocyte, neutrophil, and platelet counts, was recently investigated as a prognostic marker in several tumors. However, SII has not been reported in esophageal squamous cell carcinoma (ESCC). We evaluated the prognostic value of the SII in 916 patients with ESCC who underwent radical surgery. Univariate and multivariate analyses were calculated by the Cox proportional hazards regression model. The time-dependent receiver operating characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
171
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(188 citation statements)
references
References 28 publications
8
171
0
1
Order By: Relevance
“…The cut off level of NLR and PLR was set as follows NLR; 1.6, PLR; 117.07 according to previous reports. 16,17…”
Section: Serum Sampling and Enzyme Immunoassay For Serum Markersmentioning
confidence: 99%
“…The cut off level of NLR and PLR was set as follows NLR; 1.6, PLR; 117.07 according to previous reports. 16,17…”
Section: Serum Sampling and Enzyme Immunoassay For Serum Markersmentioning
confidence: 99%
“…Numerous prognostic factors, including TNM stage, have been reported . However, recently, inflammatory and nutritional markers such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and C‐reactive protein to albumin ratio (CAR) have been recognized as useful prognostic markers for esophageal cancer patients worldwide . Of note, the majority of these investigations were retrospective cohort studies.…”
Section: Introductionmentioning
confidence: 99%
“…The SII should be a more objective marker that reflects the balance between host inflammatory and immune responses than all the other systemic inflammation scores. Geng et al showed SII to be superior to the above indices as a prognostic predictive factor in patients with esophageal squamous cell carcinoma (8). A previous study showed that non-steroidal anti-inflammatory drugs have a role in the prevention and treatment of cancer (23) Therefore, there is a possibility that pw NSCLC who have a high SII may especially benefit from targeted anti-inflammatory with aspirin and non-steroidal anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Geng et al suggested that SII was superior to other such indices, such as NLR, and served as a more objective marker that reflects the balance between host inflammatory and immune response status in patients with esophageal squamous cell carcinoma (8).…”
mentioning
confidence: 99%